2021
DOI: 10.1002/alz.12383
|View full text |Cite
|
Sign up to set email alerts
|

Social network characteristics moderate associations between cortical thickness and cognitive functioning in older adults

Abstract: Introduction Prior research suggests that the strength of association between Alzheimer's disease (AD) pathology and lower cognitive performance is influenced by modifiable psychosocial factors, such as social network size. However, little is known about distinct social relationship types. Methods The current cross‐sectional study used data from the Washington Heights‐Inwood Columbia Aging Project to examine whether social network characteristics (i.e., total size, spouse/partner, number of children, other rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[29][30][31] For example, individuals with higher levels of social engagement, more friends, and a diverse set of associates are more resilient than similar peers, on average, to the cognitive effects of neurodegeneration. 32,33 Likewise, social network size and complexity are associated with functional connectivity between the amygdala and other brain regions and with neural response to social information, 34,35 suggesting that neural networks may be a mechanism of cognitive reserve linked to social bridging.…”
Section: Narrativementioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] For example, individuals with higher levels of social engagement, more friends, and a diverse set of associates are more resilient than similar peers, on average, to the cognitive effects of neurodegeneration. 32,33 Likewise, social network size and complexity are associated with functional connectivity between the amygdala and other brain regions and with neural response to social information, 34,35 suggesting that neural networks may be a mechanism of cognitive reserve linked to social bridging.…”
Section: Narrativementioning
confidence: 99%
“…Up to one third of older adults meeting full neuropathological criteria for ADRD exhibit no significant cognitive impairment, suggesting that even relatively advanced neurodegeneration may be masked (or moderated) by compensatory processes, including social enrichment 29–31 . For example, individuals with higher levels of social engagement, more friends, and a diverse set of associates are more resilient than similar peers, on average, to the cognitive effects of neurodegeneration 32,33 . Likewise, social network size and complexity are associated with functional connectivity between the amygdala and other brain regions and with neural response to social information, 34,35 suggesting that neural networks may be a mechanism of cognitive reserve linked to social bridging.…”
Section: Narrativementioning
confidence: 99%
“…For instance, Salinas et al (2022) demonstrated that the group experiencing loneliness exhibited poorer executive function, lower total brain volume, and greater white matter injury. Similarly, Van Der Velpen et al (2022) found that the baseline white matter volume was smaller in the lonely group. However, these studies have yielded inconsistent results, and they have the limitation of measuring loneliness using only a single item derived from the Center for Epidemiologic Studies Depression Scale (CES-D).…”
Section: Introductionmentioning
confidence: 80%
“…Studies have shown that, in general, an increase in social network size is associated with an increase in the size of the amygdala ( Bickart et al, 2011 ; Kanai et al, 2012 ; Von Der Heide et al, 2014 ). However, there have been conflicting results regarding cortical thickness ( Bickart et al, 2011 ; Sherman et al, 2016 ; Sharifian et al, 2022 ) and frontal lobe volume ( Powell et al, 2012 ; Von Der Heide et al, 2014 ). Nonetheless, findings suggest that as social network size increases, there is an increase in white matter microstructure in the frontal lobe ( Noonan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Which aspects of social engagement are most relevant for cognitive aging remains under investigation. Larger social networks seem to confer protection against cognitive decline [8,12,13], and evidence suggests that increasing social interactions is a promising intervention against cognitive decline [14][15][16]. However, the biological mechanisms mediating the impacts of social engagement on cognitive functions remains elusive.…”
Section: Introductionmentioning
confidence: 99%